Hydrological behaviour of an ice‐layered snowpack in a non‐mountainous environment - Paquotte, Andrea; Baraer, Michel (Hydrological Processes, 2022)
Abstract The increased frequency of mild rain‐on‐snow (R.O.S.) events in cold regions associated with climate change is projected to affect snowpack structure and hydrological behaviour. The ice layers that form in a cold snowpack when R.O.S. events occur have been shown to influence flowthrough processes and liquid water retention, with consequences for winter floods, groundwater recharge, and water resources management. This study explores interconnections between meteorological conditions, ice layer formation, and lateral flows during R.O.S. events throughout the 2018–2019 winter in meridional Quebec, Canada. Automated hydro‐meteorological measurements, such as water availability for runoff, snow water equivalent, and snowpit observations, are used to compute water and energy balances, making it possible to characterize a snowpack's internal conditions and flowthrough regimes. For compatibility assessment, water and energy balances‐based flowthrough scenarios are then compared to different hydro‐meteorological variables', such as water table or streamlet water levels. The results show an association between highly variable meteorological conditions, frequent R.O.S. events, and ice layer formation. Lateral flows were mainly observed during the early stage of the ablation period. The hydrologically significant lateral flows observed in the study are associated with winter conditions that are predicted to become more frequent in a changing climate, stressing the need for further evaluation of their potential impact at the watershed scale.
Keywords: Baraer_Michel; Infolettre; Infolettre_Ete_2023

A review of the current state of knowledge of proglacial hydrogeology in the Cordillera Blanca, Peru - Glas, Robin; Lautz, Laura; McKenzie, Jeffrey; Mark, Bryan; Baraer, Michel; Chavez, Daniel; Maharaj, Laura (WIREs Water, 2018)
The rapidly melting glaciers of Peru are posing new risks to regional dry season water supplies, and this is evident in the Cordillera Blanca, the mountain range with the world's largest concentration of tropical glaciers. Permanent ice loss is causing reductions to dry season streamflow, which is coupled with shifting demands and control over water access and entitlements in the region. A full evaluation of hydrologic inputs is required to inform future water management in the relative absence of glaciers. Over the last decade, new studies have shown groundwater to be a significant component of the regional water budget during the dry season, and it cannot be ignored when accounting for water quality and quantity downstream of the Cordillera Blanca's alpine catchments. Distinctive common features of the Cordillera Blanca's proglacial catchments are sediment‐filled valleys that were once under proglacial lake conditions. The combination of lake sediments with other alpine depositional features results in storage and interseasonal release of groundwater that comprises up to 80% of the valley's streamflow during the driest months of the year. We summarize the emerging understanding of hydrogeologic processes in proglacial headwater systems of the region's principal river, the Rio Santa, and make suggestions for future research that will more clearly characterize the spatial distribution of stored groundwater within the mountain range. As glaciers continue to recede, differences in aquifer thickness and groundwater residence time between alpine catchments in the region will increasingly control dry season water availability at the local and basin scale. This article is categorized under: Science of Water > Hydrological Processes Science of Water > Water and Environmental Change Engineering Water > Planning Water
Keywords: Baraer_Michel